Esophageal Perforation Associated With Fontan Operation: A Complication of Transesophageal Echocardiography. (July 2013) - Kumar, Gaurav; Provenzano, Sylvio; Alphonso, Nelson; Karl, Tom R.
A 10-year-old girl with unbalanced atrioventricular septal defect and aortic arch interruption with interrupted inferior vena cava and dextrocardia had undergone a modified Norwood procedure followed by a Kawashima operation in 2002 and 2005, respectively. In 2012, she underwent Fontan operation with diversion of hepatic veins to left pulmonary artery. Intraoperative transesophageal echocardiography (TEE) was used. She was noted to have an esophageal perforation, diagnosed on the 10th postoperative day. She was managed with thoracic drainage, cervical esophagostomy, and feeding jejunostomy. Esophageal perforation is a rare complication of TEE and requires very aggressive treatment.